2012
DOI: 10.1177/0734242x12437565
|View full text |Cite
|
Sign up to set email alerts
|

Metals bioleaching from electronic waste by Chromobacterium violaceum and Pseudomonads sp

Abstract: These days, electronic waste needs to be taken into consideration due to its materials content, but due to the heterogeneity of the metals present, reprocessing of electronic waste is quite limited. The bioleaching of metals from electronic waste was investigated by using cyanogenic bacterial strains (Chromobacterium violaceum, Pseudomonas aeruginosa and Pseudomonas fluorescens). A two-step bioleaching process was followed under cyanide-forming conditions for maximum metals mobilization. Both single and mixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(73 citation statements)
references
References 30 publications
0
53
1
2
Order By: Relevance
“…In contrast, some microorganisms such as cyanogenic or amino acid-excreting microorganisms solubilize the elemental gold by the formation of gold-complexing metabolic products acting as biogenic lixiviants [13]. Bioleaching of gold by cyanogenic bacteria has been reported [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, some microorganisms such as cyanogenic or amino acid-excreting microorganisms solubilize the elemental gold by the formation of gold-complexing metabolic products acting as biogenic lixiviants [13]. Bioleaching of gold by cyanogenic bacteria has been reported [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported bioleaching ability of Chromobacterium violaceum to mobilize diverse metals, including Zn, from solid and electronic materials [29] [30]. An unexpected result was the occurrence of a strong dominance of Escherichia in the TSC waste.…”
Section: Discussionmentioning
confidence: 95%
“…This observation corroborates a bioleaching study which showed an increase in pH (from 7 to 9) in two-step bioleaching at 1% w/v pulp density of ESM. (Pradhan and Kumar, 2012). In contrast to low pulp densities, pH gradually decreased to below 7 at higher pulp densities of 2% and 4%.…”
Section: Bacteriamentioning
confidence: 91%
“…Faramarzi et al, 2004 obtained a maximum gold dissolution of 14.9% from shredded pieces of printed circuit board by C. violaceum in one-step bioleaching (where electronic scrap was added directly to the bacterial growth medium). Another study reported that C. violaceum leached 70% of gold from electronic scrap following a two-step bioleaching protocol (Pradhan and Kumar, 2012). A direct comparison of gold recoveries from bioleaching studies is difficult since the metal composition of ESM is heterogeneous and varies with age, origin, and manufacturer, and the acid digestion protocols used by different researchers are dissimilar.…”
Section: Metal Recovery In Two-step and Spent Medium Bioleaching Withmentioning
confidence: 98%